LINGKUNGAN KELUARGA SEBAGAI SUMBER STIMULASI UTAMA UNTUK PERKEMBANGAN KOGNITIF ANAK USIA PRASEKOLAH - Elmanora, -; Hastuti, Dwi; Muflikhati, Istiqlaliyah (Jurnal Ilmu Keluarga dan Konsumen, 2017)
This study aimed to analyze the influence of child characteristic, family characteristics, quality of home environment, and quality of preschool education on child's cognitive development in Sungai Penuh City, Jambi Province. The samples were 120 children who are attending formal (formal group) and nonformal (nonformal group) preschool education and her/his mother that were selected by stratified random sampling. The samples chose from eightpreschool education (four formal and four nonformal). Data collected by interview and observation. Data analysis used descriptive analysis, independent samples t-test, and path analysis.Formal group families had higher mother’s education, family income, and the quality of home environment than nonformal group families. The quality of formal preschool education also better than the quality of nonformal preschool education. The preschool children’s cognitive development was influenced by the child's age, maternal education, family income, quality of home environment, the type of preschool education, and quality of preschool education. Stimulation from family environment had stronger effect on child's cognitive development than stimulation from school environment